The Effect of Staff Knowledge, Perceived Value, and Perceived Ease of Use on Patient Trust - Nanda Nuryani; Stefany Rota Kadang; Maghfirah Puspa Bhara Umar (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of Staff Knowledge, Perceived Value, and Ease of Use on Patient Trust in hospitals. Patient trust is a crucial factor in increasing satisfaction and sustainability of health services. This study uses Structural Equation Modeling (SEM) with Partial Least Squares (PLS) as an analysis method to test the relationship between the constructs involved. Data were obtained from 100 hospital patient respondents using random sampling techniques, and the analysis was carried out using SmartPLS software. The results showed that Perceived Value had the greatest influence on Patient Trust, with a Path Coefficient of 0.46, followed by Staff Knowledge (0.32) and Ease of Use (0.28). All tested relationships showed high significance with a p-value of less than 0.05. However, several constructs, especially Staff Knowledge and Perceived Value, showed problems in reliability and validity, indicating the need for improvement of the indicators used. In conclusion, this study emphasizes the importance of improving the quality of Staff Knowledge, strengthening Perceived Value, and providing more accessible services to increase Patient Trust. Improvements to constructs with low reliability need to be made to ensure more valid and reliable measurements.